Effect of light, pH, metal ions and antioxidants on the colour stability of norbixin in aqueous solution. (23rd November 2018) - Møller, Anders Hauer; Jahangiri, Amita; Madsen, Bjoern; Joernsgaard, Bjarne; Vaerbak, Signe; Hammershøj, Marianne; Dalsgaard, Trine Kastrup
Summary: Norbixin, a carotenoid extracted from the seeds of the annatto ( Bixa orellana ) plant, can be used in aqueous food applications, where other carotenoids are too hydrophobic to solubilise in a water environment. The aim of this work was to investigate the effect of pH, antioxidants and transition metal ions with and without hydrogen peroxide (H2 O2 ) on the stability of norbixin in aqueous solutions as well as determining the interaction between these factors and light. The stability of norbixin in buffered aqueous solution stored in light or in the dark was evaluated using absorbance spectrophotometry. Light, reduced pH and metal ions both with and without H2 O2 increased the bleaching of norbixin, whereas chelators and the natural antioxidants, ascorbic acid and tocopherol, reduced the bleaching of norbixin. Light significantly increased the loss of norbixin alone and in combination with the other factors. Abstract : The effect of pH, metal ions, metal chelators and antioxidants on the stability of aqueous norbixin was tested in both light and dark. All tested factors affected the stability of norbixin and light increased the norbixin bleaching alone and when combined with the different factors.